The Influence of Supervisor Developmental Feedback on Employee Innovative Behavior: A Moderated Mediation Model - Su, Weilin; Lin, Xinqi; Ding, He (Frontiers in Psychology, 2019)
Previous scholars have recognized the critical role of supervisor in stimulating employee innovative behavior, while it is still unclear whether and how supervisor developmental feedback impacts employee innovative behavior. To resolve this issue, the present study develops and verifies a moderated mediation model to explore the positive influence of supervisor developmental feedback on employee innovative behavior via creative self-efficacy, as well as the moderating role of supervisor’s organizational embodiment in this process. Analyses of the multi-time data from 375 employees indicate that supervisor developmental feedback is positively associated with employee innovative behavior via his/her creative self-efficacy. Moreover, supervisor’s organizational embodiment moderates the influence of supervisor developmental feedback on employee creative self-efficacy and the mediating role of creative self-efficacy. From these analyses, the present study not only further develops several views of pervious researches in the flied of supervisor feedback and employee innovation, but also provides a potential managerial way to promote employee innovative behavior from the perspective of supervisor feedback.